Efficacy of switching from originator adalimumab to biosimilar adalimumab-AACF in patients with axial spondyloarthritis: a 12-month observational study - Fanny Alcira Reyes Neira; Barbara Bayeh; Karina Rossi Bonfiglioli; Nadia Emi Aikawa; Ana Paula Luppino Assad; Renata Miossi; Fernando Henrique Carlos de Souza; Carlos Emilio Insfrán; Henrique Ayres Mayrink Giardini; Emily Figueiredo Vieira Neves Yuki; Eloisa Bonfa; Carla Gonçalves Schahin Saad; et al. (Exploration of Musculoskeletal Diseases)
Aim: The use of anti-TNF drugs is well-established for treating axial spondyloarthritis (axSpA). The introduction of biosimilars offers a more accessible alternative, but data on the switching of adalimumab biosimilars in the axSpA population remain somewhat controversial and are limited to SB5 and ABP 501 and to the European population. This study aims to evaluate the clinical efficacy of switching from originator adalimumab to the biosimilar adalimumab-AACF in Latin American axSpA patients over a 12-month period in a real-life analysis. Methods: This observational study included patients with axSpA who had been treated with originator adalimumab for at least three months and switched to the biosimilar. Disease activity parameters and C-reactive protein (CRP) levels were assessed at baseline (T0) and compared at 6 (T6) and 12 months (T12) following the switch. Results: Twenty-eight patients were included, with a mean duration of originator adalimumab use of 87.6 months. Ankylosing Spondylitis Disease Activity Score (ASDAS)-CRP remained stable when comparing T0 to T6 [1.56 (± 0.88) vs. 1.50 (± 0.82), P = 0.73] and T12 [1.56 (± 0.88) vs. 1.26 (± 0.86), P = 0.13]. A similar pattern was observed for ASDAS-erythrocyte sedimentation rate (ESR; P > 0.05) and Bath Ankylosing Spondylitis Disease Activity Index (BASDAI; P > 0.05). The rate of remission/low disease activity was consistent, recorded at 71.4% at baseline, 78.6% at T6 (P = 0.62) and 78.6% at T12 (P = 0.68). CRP levels did not show significant variation (P > 0.05) across time points. Notably, the one-year drug retention rate was 94.6%. Conclusions: This real-world study highlights for the first time the feasibility and efficacy of transitioning from originator adalimumab to biosimilar AACF in axSpA, providing support for its use in long-term management and offering enhanced accessibility without compromising therapeutic outcomes. These results add valuable Latin American data to the body of evidence on biosimilar integration into clinical practice.